Size and location of posterior wall fragment on CT can predict hip instability in a cadaveric model. Issue 8 (August 2021) - Apivatthakakul, Theerachai; Koerner, Jason L.; Luangsod, Sutiwat; Buranaphatthana, Thanawat; Parry, Joshua; Hadeed, Michael; Funk, August; Stacey, Stephen; Mauffrey, Cyril
Highlights: A fracture size of 15% and fracture angle of 40° were stable on EUA All fracture sizes above 15% and fracture angles greater than 40 degrees were unstable on EUA The use of CT to evaluate posterior wall acetabulum fractures could be a beneficial tool to aid providers in determining need for EUA Abstract : Purpose: Previous research has been unable to elucidate the exact factors that contribute to hip instability in the setting of posterior wall acetabular fractures. The purpose of this study was to determine the influence of posterior wall fracture fragment size and fracture angle on the stability of the hip joint in a cadaveric model. Methods: Six fresh human cadavers (12 hips) were used. Specimens underwent pre-procedure CT evaluation and were then randomized to one of three groups: posterior wall fragment size (FS) of 15%, 20% and 25%. Osteotomies were performed starting at a fracture angle (FA) of 40°. The specimens underwent an exam under anesthesia (EUA). If the hip remained stable, the fracture angle was increased in 20° increments and re-tested until it became unstable. Results: In the group with a FS of 15%, all hips were stable with a FA of 40°. Increasing the FA to 60° caused all hips to be unstable (subluxation or dislocation). In the group with a FS of 20% and 25%, all hips were unstable with a FA of 40°. Conclusion: In all specimens, a FS of 15% and FA of 40° were stable on EUA. Varying combinations of increasing FS size and increasing FA were all unstable. This study provides data for a CT-based measurement to predict hip instability in the setting of posterior wall acetabular fractures based on FS and FA. More research is required to validate this data in a clinical setting.